Principles of Shaping and Composition of the Management Staff of Polish Industry (1945–1956) - Chumiński, Jędrzej (Studia Historiae Oeconomicae, 2023)
Numerous studies on the economies of socialist countries indicate that one of the main sources of their weakness was the attitudes and behavior of “socialist managers”. Contrary to the predictions (e.g. by Joseph Schumpeter), they were not characterized by entrepreneurship, innovation, the ability to lead changes or the ability to formulate strategies. This was due to the nomenclature system existing in all countries of the Soviet bloc. Nominations, promotions, but also dismissals were at the discretion of party bodies. It was the main source of the communist party’s dominance in the country and the fundamental factor guaranteeing control over all spheres of social and economic life. Determining why the nomenclature system turned out to be dysfunctional requires considering three issues: what were the goals of the communist personnel policy, what methods were used to implement it, and finally who were the people appointed to perform managerial functions in the economy. We will focus our analysis on the management of Polish industry in the years 1945–1956. This is because it was the most important sector of the economy of the People’s Republic of Poland, and the personnel policy mechanisms developed at that time remained valid until the end of the “real socialism” system.